Importance of Social Media in Online Marketing and Use of Eye-Tracking Methods in Online Shopping - Daria Rudkova 1991- (2015)
The main objective of this study is examining how different attributes, presented in Internet sales on Facebook, can influence a consumer’s behavior. The study was done in collaboration with a fashion store called Mania and a marketing and research company called MMR. An emphasis was imposed on five independent variables, the position of the price and size tags, whether the size and price were mentioned or not and the prevalence of a human model. In addition to that, the total fixation time was explored, in regards to a difference between men and women. Tobii’s 1750 eye scanner device was used in real life setting to measured how much the attributes affected the total fixation time participants had on the product. Participants in the study were students at Reykjavik University in the year 2014. A hierarchical multiple regression was done to test if the main attributes in the study significantly predicted the length of the total fixation time. The results showed that three out of five independent variables had a significant impact on the dependent variable or the total fixation time. The results also showed that there was a significant difference between male and female fixation duration, with male participants in general looking longer than female participants. Based on the results it can be concluded that the prevalence of the human model, and when size is not revealed, has a positive effect on the participant‘s attention duration. Meginmarkmið þessarar rannsóknar er að kanna hvernig mismunandi eiginleikar, sem koma fram í netsölu á Facebook, hafa áhrif á hegðun neytenda. Rannsóknin var gerð í samstarfi við fataverslunina Maníu í Reykjavík og markaðs og miðlunar fyrirtækið MMR. Athugað var hvernig staðsetning á verði og stærð verðmiðans hafi áhrif á skynjun neytandans hvort verð og stærð vörunnar væru tekin fram og hvort tilvist fyrirsætu hafi áhrif á heildar skynjun neytandans. Einng var athugað hvort munur væri á skynjun á milli kynja. Notast var við Tobii 1750 augnskanna til þess að mæla skynjun ...